2007
DOI: 10.1145/1189736.1189739
|View full text |Cite
|
Sign up to set email alerts
|

Trace cache sampling filter

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…A successful implementation of updating filtering can be conducive in reducing the table sizes and/or improve their performance. CATCH employs a simple but effective filtering scheme proposed by Behar et al [1]. The filtering is accomplished by allowing a table to be updated every n attempts.…”
Section: Performance Optimizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A successful implementation of updating filtering can be conducive in reducing the table sizes and/or improve their performance. CATCH employs a simple but effective filtering scheme proposed by Behar et al [1]. The filtering is accomplished by allowing a table to be updated every n attempts.…”
Section: Performance Optimizationsmentioning
confidence: 99%
“…This policy works because it can prevent rare events from entering the tables, whereas persistently occurring events will eventually make it into the table. For an extended discussion on how this method works we refer the interested reader to [1]. Based on simulation results, not shown here, it was found that the best strategy was to filter only the updates of the HDD and the filter value should be four, i.e.…”
Section: Performance Optimizationsmentioning
confidence: 99%
“…The only study that used some form of sampling was done by Behar et al [2]. As programs are known to spend most of the time executing a small portion of the code, they observed that generating only 1 in 10 traces for the trace cache does not hinder performance and reduces the power consumption of the trace generating unit.…”
Section: Identifying the Core Working Setmentioning
confidence: 99%